Analysis of Students' Analytical Thinking Skills in Responding to the Development of the Industrial Revolution 4.0 - Fakhrurrazi, Fakhrurrazi; Sajidan, Sajidan; Karyanto, Puguh (Proceedings of International Conference on Biology and Applied Science; Vol 1 No 1 (2019): The First Proceedings of International Conference on Biology and Applied Science, 2019)
Abstract. Competitiveness in the era of industrial revolution 4.0 requires students have more thinking skills, especially in solving problems related to local and global issues. One way is through learning process by empowering analytical thinking skills. This study aims to determine the profile of analytical thinking skills of MAN 2 Surakarta students. The subjects in this study were 90 students consisting of 3 classes. The instrument used in this study was a test using multiple choice questions developed based on indicators of analytical thinking skills according to Marzano and Kendall. Data were analyzed by qualitative descriptive method. Based on data analysis, the average analytical thinking skills of students were obtained by 43.8% (low category). The percentage of adjustment aspects was 51.3% (low category), the classification aspect was 46.0% (low category), the error analysis aspect was 39.4% (very low category), the generalization aspect was 47.6% (low category), and the specification aspect 30% (very low category). The results of this study provide information the profile of analytical thinking skills of students is still low, so the teacher is expected be able to design a learning process that can empower students' analytical thinking skills in responding development of industrial revolution 4.0 era.